2016
DOI: 10.4093/dmj.2016.40.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Is Associated with Impaired Muscle Quality in Older Men with Diabetes: The Korean Longitudinal Study on Health and Aging

Abstract: BackgroundThe study aimed to investigate the influence of hyperglycemia on muscle quality in older men with type 2 diabetes.MethodsThis was a subsidiary study of the Korean Longitudinal Study of Health and Aging. Among 326 older men consenting to tests of body composition and muscle strength, 269 men were ultimately analyzed after the exclusion because of stroke (n=30) and uncertainty about the diagnosis of diabetes (n=27). Body composition was measured using dual-energy X-ray absorptiometry and computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 29 publications
2
69
3
2
Order By: Relevance
“…Therefore, a novel contribution of the present study is that it clarifies a linear relationship between hyperglycemia, as assessed by HbA1c levels, and the frequency of sarcopenia in patients with diabetes. The present results further clarified that the harmful effect of hyperglycemia was specific to SMI and not associated with physical performance, namely grip strength and gait speed, as well as muscle quality; in contrast, previous studies found lower physical performance and physical functional decline in patients with diabetes in comparison with non‐diabetic controls. A reason for the discrepancy might be the different study setting; that is, previous studies found lower physical performance in patients with relatively mild diabetes, suggesting that functional decline in physical performance might precede muscle mass decline.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, a novel contribution of the present study is that it clarifies a linear relationship between hyperglycemia, as assessed by HbA1c levels, and the frequency of sarcopenia in patients with diabetes. The present results further clarified that the harmful effect of hyperglycemia was specific to SMI and not associated with physical performance, namely grip strength and gait speed, as well as muscle quality; in contrast, previous studies found lower physical performance and physical functional decline in patients with diabetes in comparison with non‐diabetic controls. A reason for the discrepancy might be the different study setting; that is, previous studies found lower physical performance in patients with relatively mild diabetes, suggesting that functional decline in physical performance might precede muscle mass decline.…”
Section: Discussionsupporting
confidence: 75%
“…Previous cross-sectional studies that reported a harmful effect of diabetes on sarcopenia [3][4][5][6]9,10 were based on findings that the frequency of sarcopenia was significantly higher in patients with diabetes than in non-diabetic control participants. However, no studies have reported whether the frequency of sarcopenia was increased by exacerbation of glycemic control in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients were additionally divided into subgroups according to level of metabolic control. HbA1c = 8.5%, similar to the studies by Onishi et al, [38] Yoon et al, [39] Christie et al, [40] and Cakmak et al, [41] was regarded as a reference value. In this way 4 subgroups were created: with good metabolic control HbA1c ≤8.5%, subgroup D1-a, n = 14, mean HbA1c 7.45 ± 1.01%; subgroup D2-a, n = 14, mean HbA1c 7.37 ± 0.78% and poor metabolic control HbA1c >8.5%, subgroup D1-b, n = 16, mean HbA1c 9.75 ± 0.95%; subgroup D2-b, n = 15 mean HbA1c 9.45 ± 0.72%.…”
Section: Methodssupporting
confidence: 62%
“…Given that insulin is a potent stimulator of growth and protein synthesis for many cells (8), insufficiency of insulin action in diabetes mellitus likely contributes to muscle mass decline; mouse models in which insulin action is genetically ablated manifest age-dependent decline of muscle mass and physical performance (9,10). Hyperglycemia, a central disorder of diabetes mellitus, is also implicated in the pathogenesis of decline in mass and function of skeletal muscle on the basis of a population-based cohort study and cross-sectional surveys of individuals with type 1 or type 2 diabetes mellitus (5,(11)(12)(13), but the underlying mechanism responsible for this relationship remains unknown.…”
Section: Introductionmentioning
confidence: 99%